The Application of Classroom Management in Increasing Learning Effectiveness - Riskawati, Riskawati; Juliana, Ana; Arfianti, Arfianti; Anti Kinas, Arni (DIDAKTIKA, 2023)
This study aims to determine the application of classroom management in improving learning at SDN 198 Cinennung Kec. China District. Bone. The important thing studied in this thesis is to find out the application of classroom management, the effectiveness of learning and the application of classroom management to increase the effectiveness of learning at SDN 198 Cinennung Kec. China District. Bone. To facilitate solving the problems above, field research is used (Field Research) using techniques such as observation, interviews (interviews) and documentation. The data obtained were analyzed using qualitative descriptive analysis with three stages, namely the data reduction stage (data reduction), data presentation (data display), and conclusion drawing/verification.